Beyond Intermediates: The Role of Consumption and Commuting in the Construction of Local Input–Output Tables. Issue 3 (2nd July 2016) - Hermannsson, Kristinn
Abstract: Estimating intermediate trade using conventional non-survey methods produces biased results. This problem has led to a methodological recommendation that emphasizes the accurate estimation of intermediate trade flows. This paper argues for a qualification of the consensus view: when simulating input–output (IO) tables, analysts need also to consider spillover effects driven by wage and consumption flows. In particular, for metropolitan economies, capturing wage and consumption flows is essential to obtain accurate Type II multipliers. This is demonstrated by constructing an interregional IO table that captures the interdependence between a city and its commuter belt, nested within the wider regional economy.